THE FEASIBILITY STUDY OF ACTIVATED CARBON DERIVED FROM INDUSTRIAL BIOMASS WASTE FOR HEAVY METAL IONS REMOVAL - YOONG ZHAN HAO, KLIFF (IRC, 2017)
This project is the continuation of Student Industrial Project (SIP) from a glove manufacturing plant, which was to study the adsorption capability of carbon derived from Biomass comprises of Rubberwood and Oil Palm Short Fiber. In this current project, further study on the biomass carbon will be conducted, from synthesis of activated carbon (AC) from the mentioned biomass with different carbonizing temperature, impregnation ratio and carbonizing time and comparison with the raw carbon from industry’s boiler is conducted; physical characterization, isotherm and kinetic analysis of the AC is done; The metal ions being emphasized include Zinc ions (Zn2+), which is the metal ion from Glove manufacturing process. Also, the project will take the opportunities to test for removal of Lead ions (Pb2+) and Nickel ions (Ni2+), from electroplating and metal surface treatment industries, using the AC synthesis.